MARRIAGE COSTS AND CULTURAL POVERTY: A PHENOMENOLOGICAL STUDY OF BATAK SOCIETY - Ivan Santono M. T. Hutapea; Izza Mafruhah; Sarjiyanto Sarjiyanto (Jurnal Ilmu Ekonomi dan Pembangunan, 2026)
Cultural poverty in developing societies often emerges from adherence to traditional practices that impose significant economic burdens on communities. In Batak Toba society, the sinamot (bride price) tradition has evolved from a symbolic gesture of respect into a status marker, creating substantial financial pressures on families. While culturally significant within the dalihan na tolu kinship system, contemporary sinamot practices frequently exceed families' economic capabilities, potentially perpetuating cycles of poverty. This study examines how the sinamot tradition contributes to cultural poverty formation in Batak Toba communities and explores community perceptions regarding this phenomenon. The research contributes to understanding cultural poverty as a product of culturally sanctioned practices rather than character deficiencies, offering insights for developing culturally sensitive poverty alleviation approaches. This qualitative study employed a phenomenological approach, conducting in-depth interviews with seven informants including married couples, parents, and traditional leaders aged 40-65 years, with data analyzed using NVivo 12 Pro software following Miles and Huberman's interactive model. The findings reveal that sinamot functions dually as both a symbol of honor (hasangapon) and an economic burden, with three primary mechanisms driving cultural poverty: social pressure to maintain high sinamot values as markers of family status, consumerist tendencies in wedding celebrations where families host grand events beyond their means, and compliance with traditional values motivated by fear of social sanctions. Sinamot amounts vary significantly based on bride's education level, ranging from IDR 10-15 million for high school graduates to IDR 20-150 million for master's degree holders, excluding additional celebration costs. Families frequently incur debts requiring two to three years to repay, limiting investments in education, health, and productive endeavors. The study identifies emerging shifts among younger generations adopting more realistic attitudes toward sinamot while maintaining cultural respect, and some traditional communities have begun simplifying ceremonial requirements. Theoretically, through Baudrillard's consumerism theory and Bourdieu's symbolic capital concept, traditional celebrations have transformed into arenas for symbolic consumption serving as social signifiers rather than authentic cultural expressions. Cultural poverty in Batak society emerges not from ignorance but from adherence to culturally legitimate practices, requiring dialogue between traditional leaders and communities to balance cultural preservation with economic sustainability.